Retrieval practice enhances the accessibility but not the quality of memory - Sutterer, David W.; Awh, Edward (Psychonomic bulletin & review, 2016)
Numerous studies have demonstrated that retrieval from long-term memory (LTM) can enhance subsequent memory performance, a phenomenon labeled the retrieval practice effect. However, the almost exclusive reliance on categorical stimuli in this literature leaves open a basic question about the nature of this improvement in memory performance. It has not yet been determined whether retrieval practice improves the probability of successful memory retrieval or the quality of the retrieved representation. To answer this question, we conducted three experiments using a mixture modeling approach (Zhang & Luck, 2008 ) that provides a measure of both the probability of recall and the quality of the recalled memories. Subjects attempted to memorize the color of 400 unique shapes. After every 10 images were presented, subjects either recalled the last 10 colors (the retrieval practice condition) by clicking on a color wheel with each shape as a retrieval cue or they participated in a control condition that involved no further presentations (Experiment 1 ) or restudy of the 10 shape/color associations (Experiments 2 and 3 ). Performance in a subsequent delayed recall test revealed a robust retrieval practice effect. Subjects recalled a significantly higher proportion of items that they had previously retrieved relative to items that were untested or that they had restudied. Interestingly, retrieval practice did not elicit any improvement in the precision of the retrieved memories. The same empirical pattern also was observed following delays of greater than 24 hours. Thus, retrieval practice increases the probability of successful memory retrieval but does not improve memory quality.